A large piezoelectric response in highly-aligned electrospun poly(vinylidene fluoride/trifluoroethylene) nanofiber webs for wearable energy harvesting. (8th October 2020) - Barique, Mohammad A; Neo, Yoichiro; Noyori, Masaji; Aprila, Lia; Asai, Masaya; Mimura, Hidenori
Abstract: In this study, highly-aligned and molecularly oriented poly(vinylidene fluoride/trifluoroethylene) [P(VDF/TrFE)] nanofiber webs were fabricated and their piezoelectric response was investigated. Using systematic post-treatments under appropriate conditions, a significant enhancement of the piezoelectric response in the P(VDF/TrFE) nanofiber webs was observed for the first time. The high-quality nanofibers exhibited a large output voltage of 0.4 V. The short-circuit current of post-treated nanofibers was found to be 731.25 μ A, which increased about 330 times and the surface electric charge density was found to be 0.64 nC cm −2, which was about 2.7 times higher than those of the as-spun nanofibers. The large enhancement of piezoelectric response of the nanofibers is attributed to the additional stretching, annealing and poling of the as-spun nanofibers under the appropriate post-treatment conditions. The results highlight the potential of the high-quality P(VDF/TrFE) nanofibers to be used as wearable piezoelectric energy harvesters and other flexible self-powered portable devices.